An integrated approach for supplier selection in multi-item/multi-supplier environment - KILIÇ, HÜSEYİN SELÇUK (ELSEVIER SCIENCE INC, 2013)
One of the important stages in supply chain management which regards all the activities from the purchasing of raw material to final delivery of the product is the supplier selection process. Since it is the first stage of the supply chain management, it is a critical process affecting the consecutive stages. It is simply desired to select the best supplier for a specific product. But since there are a lot of criteria and alternatives to be considered, numerous decision making models have been proposed to provide a solution to this problem. Within this study, an integrated approach including fuzzy Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) and a mixed integer linear programming model is developed to select the best supplier in a multi-item/multi-supplier environment. The importance value of each supplier with respect to each product is obtained via fuzzy TOPSIS in the first stage. Then in the second stage, these values are used as an input in the mathematical model which determines the suppliers and the quantities of products to be provided from the related suppliers. So as to validate the proposed methodology, an application is performed in air filter sector. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Supplier selection; Supply chain management; Fuzzy TOPSIS; Mixed integer linear programming; DECISION-SUPPORT-SYSTEM; FUZZY TOPSIS; AXIOMATIC DESIGN; MODEL; CRITERIA; NETWORK; VIKOR; AHP